Oxford-River Books English-Thai dictionary - Parima Manlikamat; Narisa Chakrabongse M. R.; Phaisan Piammettawat; Chulaalongkonmahawitthayalai (Great Clarendon Street, Oxford Oxford University Press : River Books, 2010)
This English-Thai dictionary is intended primarily as a reference work and useful resource for students of the English language, but has attempted to meet the needs of varying groups of users by providing the most complete definitions of words and idioms possible.
Keywords: English language -- Dictionaries -- Thai